Surgical Management of Gastric Cancer: An Institutional Experience - Sharma, Anup; Thapa, Pradip (Journal of Nepalgunj Medical College, 2019)
Introduction: Gastric cancer (GC) is the second most common cause of cancer-related deaths causing about 800,000 deaths worldwide/year. In Nepal gastric cancer is the second common cancer among males after the lung cancer. Gastric cancer shows a wide variation in incidence worldwide, being highest in Korea and Japan. It is detected early due to the low threshold for upper gastrointestinal endoscopy and screening programs. In the rest of the world and particularly in developing countries, GC is advanced in most of the cases. Inspite of controversies in extent of resection and lymphadenectomy, surgery remains the gold standard treatment. The study was conducted to determine the outcome of the patients with gastric cancer. Methods: The study was conducted in the department of surgery at Nepalgunj Medical College and Teaching Hospital Kohalpur from November 2015 to Dec 2018. Patients diagnosed with GC were studied. The patients with resectable disease underwent radical resection followed by adjuvant chemo-radiation as indicated. Patient’s demography, clinical presentation, stage of disease, types of surgery performed and survival were analysed. Results: 58 patients were diagnosed with gastric cancer. The age ranged from 20-83 years with the mean of 61.26±11.28. Male to female ratio was 2.41: 1. The common clinical presentations were weight loss, anorexia and anemia, 17 (29.31%) had gastric outlet obstruction at initial presentation and 4 (6.89%) presented with perforation peritonitis. Antropyloric region was the commonest site of tumor location seen in 41 (70.68%). 7 (12.06%) patients had distant metastasis and 5 (8.62%) had ascites at presentation. Out of 58 patients, 43 (74.13%) were operated. Only 18 (41.86%) patients underwent R0 resection. 14 (24.13%) underwent palliative gastrojejunostomy. Two (3.44%) patients underwent primary repair for perforation and in 9 (15.51%) the procedure was abandoned due to and presence of metastasis. There was one post-operative mortality. The histology of gastric cancer was found to be adenocarcinoma in all patients. There was no patient in stage I. 3(16.66%) patients were in stage II and 15 (83.33%) in stage III. 17 (29.31%) had stage IV disease. Out of 43 operated patients, 13 lost follow up. All 17 resected patients and those with metastatic disease were followed up. There was no death and no local recurrence in stage II. In stage III, 78.57% were alive and in stage IV 35.29% were alive. Conclusion: Gastric cancer is one of the common gastrointestinal malignancies affecting predominantly male gender. Stage of the disease is one of the major prognostic factors related with the survival. Adenocarcinoma is the commonest histology. Radical resection followed by adjuvant chemotherapy is the standard of care. Palliative chemotherapy can prolong the overall survival in patients with metastatic disease.